2010
DOI: 10.1021/la103937f
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Hexagonal Sb2Te3 Nanoplates into Nanorings Driven by Growth Temperature

Abstract: We describe a novel route for the conversion of hexagonal Sb(2)Te(3) nanoplates into nanorings driven by growth temperature in a simple solvothermal process. The transmission electron microscopy was employed to investigate systemically the morphology, size, crystallinity, and microstructure of the as-prepared products. The experiments indicated that the growth temperature had a great effect on the morphology of antimony telluride nanostructures. When the experiments were conducted at 200 °C, the hexagonal anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Previous reports indicated that a higher density of imperfections, such as surface roughness, [35] planar defects, [36] and a high surface tension, [38] exist near the center of the nanoplates. The imperfections reduce the dissolution energy of the nanocrystals, and thus a higher dissolution rate is possible in the center of the nanoplates (Figure 3(c)).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous reports indicated that a higher density of imperfections, such as surface roughness, [35] planar defects, [36] and a high surface tension, [38] exist near the center of the nanoplates. The imperfections reduce the dissolution energy of the nanocrystals, and thus a higher dissolution rate is possible in the center of the nanoplates (Figure 3(c)).…”
Section: Resultsmentioning
confidence: 98%
“…Both internal crystal factors and external factors, such as the additives [32], reaction time [5,33] and reaction temperature [34][35][36] should be considered.…”
Section: Resultsmentioning
confidence: 99%
“…3g-j, a few microflakes are synthesized on the surface of the CC at the reaction time of 0.5 h. With the increase of the reaction time, the center area of the microflakes becomes gradually thin, and forms a hole at the reaction time of 2.5 h. They are called microring. Whose morphology is analogous to the porous NiCo 2 O 4 hexagonal ring-graphene hybrid [28], which is attributed to the chemical etching induced by the excessive amounts of NH 4 F [29,30]. With the help of NH 4 F, the nanowires will grow on microrings.…”
Section: Resultsmentioning
confidence: 99%
“…5(c)) strengthen this assumption. The strainfield surrounding such dislocations could already have been present in the PbTe host lattice providing the location for precipitate formation [14].…”
Section: Temmentioning
confidence: 99%